2009
DOI: 10.1111/j.1745-6592.2009.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Polar Compounds from the Dissolution of Weathered Diesel

Abstract: Hydrocarbon and nonhydrocarbon components dissolving in water from fresh diesel and field samples of highly weathered diesel (spilled up to 50 years ago) from two sites were investigated. The fresh and weathered diesels were equilibrated with water using a slow‐stirring method, and the product and equilibrated aqueous water samples analyzed by a range of analytical procedures. The water phase equilibrated with weathered diesels had higher total dissolved organics concentrations (96 and 8.6 mg/L at the two site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…The polar compounds were typically found in groundwater directly within the source area and downgradient from biodegraded petroleum; therefore, it was concluded that they were most likely biodegradation metabolites. This finding was confirmed by Lundegard and Sweeney (), Haddad et al (), and Lang et al (). These studies showed that the concentration of polar metabolites, quantified as TPHd, typically ranged from 100s to 10,000s micrograms per liter (µg/L), with a maximum of about 100,000 µg/L.…”
Section: Introductionsupporting
confidence: 70%
“…The polar compounds were typically found in groundwater directly within the source area and downgradient from biodegraded petroleum; therefore, it was concluded that they were most likely biodegradation metabolites. This finding was confirmed by Lundegard and Sweeney (), Haddad et al (), and Lang et al (). These studies showed that the concentration of polar metabolites, quantified as TPHd, typically ranged from 100s to 10,000s micrograms per liter (µg/L), with a maximum of about 100,000 µg/L.…”
Section: Introductionsupporting
confidence: 70%
“…This finding is consistent with results from other studies (Zemo and Foote ; Lundegard and Sweeney ; Lang et al. ; Zemo et al. ).…”
Section: Resultssupporting
confidence: 94%
“…This article is provided as a “technical note” contribution because the larger issue of polar compounds in groundwater at petroleum release sites has been published elsewhere (Zemo and Foote ; Lundegard and Sweeney ; Lang et al. ; Zemo et al ). This article focuses only on the SGC itself, and compares results from two different but commonly used SGC methods.…”
Section: Introductionmentioning
confidence: 99%
“…These peaks may include unaltered but also altered compounds (residues) which can, in moderate to extreme cases, produce a hump consisting of an unresolved complex mixture of residues evident in the chromatogram at higher retentions (temperature). Furthermore, depending on the way TPH is carried out, the extent of contamination may be underestimated in terms of the unresolved diesel residues resulting from biodegradation (Lang et al, 2009).…”
Section: Organic Contaminantsmentioning
confidence: 99%